Ultracompact Silicon Waveguide Bends Designed Using a Particle Swarm Optimization Algorithm - Po-Han Fu; Chen-Yu Chao; Ding-Wei Huang (IEEE Photonics Journal)
In this study, the trajectory of a 90° bend is divided into two symmetric halves that are mirror images of each other as referenced to the symmetry axis at 45°, and each half is segmented into small curved sections. The bending radius and waveguide width for every section are parameters to be determined using a particle swarm optimization algorithm. The optimization is performed to maximize the transmission of the waveguide bends, which is calculated by using the three-dimensional finite-difference time-domain technique. The results indicate that the total bending loss of the optimized 90° bends with radii of 2, 3, 4, and 5 μm are 0.0106, 0.0051, 0.0025, and 0.0023 dB, respectively, at the wavelength λ = 1550 nm. In addition, the optimal devices are fabrication tolerant, with fabrication errors in width and height within 10 nm, and less wavelength-dependent compared with circular bends.